A survey on the reading habits of the english language teachers in secondary schools in Kuching - Samarahan division in Sarawak - John, Rudi (Universiti Malaysia Sarawak, (UNIMAS), 2003)
This study was conducted to determine the reading habits of the English Second Language (ESL) teachers in fifteen secondary schools in Kuching-Samarahan Division in Sarawak. In relation to that, this study seeks to find out the types of materials the English Second Language (ESL) teachers read and find out how much time they spend on reading. At the same time, this study also seeks to find out the factors that influence the English Second Language (ESL) teachers' reading habits. This includes the factors that encourage and discourage reading. Finally. this study also aims to ascertain the English Second Language (ESL) teachers' perceptions on their reading habits. The survey is employed in this study. The study had random samples of 150 English Second Language (ESL) teachers from fifteen secondary schools in Kuching-Samarahan Division in Sarawak. The findings of this study reveal that the English Second Language (ESL) teachers are not inclined in reading materials related to their job. On the other hand materials not related to job are widely read. The findings of this study also revealed that leisure activities such as doing housework and entertainment like television watching and listening to radio was seen to compete in time to reading. The findings of this study also revealed that an alternative source of information such as Internet is an increasing popular source for knowledge and access to teaching and learning materials. This means that the reading habits of the English Second Language (ESL) is now shifting from print media to electronic media such as Internet via computers.